Traffic effects of locating grocery stores: - environmental and economic effects of locating shopping centres outside of the C.B.D. - Murto, Risto (Proceedings from the Annual Transport Conference at Aalborg University, 1996)
Recent policy in Finland regarding retail trade for daily products has been to invest in large shopping centres and hypermarkets located outside main city areas, often close to traffic interchanges. This has led to a number of problems. Small local shops located in the city have had difficulties in surviving. Often these large shopping areas can only be reached by car, which causes problems for those without private transportation possibilities. For retailers, however, these centres represent a logistically efficient way to operate with respect to both goods supply and customer demand. Thus, the traffic effects and the economic and environmental efficiency of such strategies can be questioned. Is it from the vantage point of society better to make longer but less frequent trips compared to the older pattern of frequent local trips? This study examined different locational alternatives: large shopping areas outside the city versus shops located at various places throughout the city and an alternative, where shopping is partly done by electronic commerce with home deliveries. The aim was to measure and compare the traffic effects of these approaches. As a result it was found out that locating four new hypermarkets in the region would increase the yearly mileage of private car traffic and goods transport by 6 percent. The land-use alternative, where there were no hypermarkets, would decrease the yearly mileage by 25 percent and the land-use alternative of home shopping would decrease the yearly mileage by 17 percent.